COVID-19 vaccination attitudes, values and intentions among United States adults prior to emergency use authorization. Issue 19 (6th May 2021) - Salmon, Daniel A.; Dudley, Matthew Z.; Brewer, Janesse; Kan, Lilly; Gerber, Jennifer E.; Budigan, Haley; Proveaux, Tina M.; Bernier, Roger; Rimal, Rajiv; Schwartz, Benjamin
Highlights: A large segment of the public is choosing to "Wait and Learn" about COVID-19 vaccine. Values and lived experience are how communities decide about COVID-19 vaccine. Pandemic conditions impact decision-making for those considering getting a vaccine. Abstract: Introduction: Safe and effective vaccines against Coronavirus Disease 2019 (COVID-19) provide the best opportunity to control the pandemic. Having safe and efficacious vaccines available is only half the equation; people must also take them. We describe a study to identify COVID-19 vaccine attitudes, values and intentions immediately preceding authorization of COVID-19 vaccines in the US. Methods: A national panel survey was conducted to measure intent to receive COVID-19 vaccines as well as disease and vaccine attitudes, values and trust in local, state and federal public health authorities. Results: Greater than 80% of respondents reported confidence they could adhere to COVID recommendations such as mask wearing, social distancing and hand washing. The majority of respondents (70%) reported believing that current drugs were somewhat or very good at treating COVID-19 infection. Vaccine intent fell into three groups: Intenders (50%), Wait and Learn (40%), and Unlikelys (10%). Intent to get vaccinated was substantially lower among African American (32%), and higher among men (56%), those over 60 years of age (61%), those with a Bachelor's degree or higher (63%), and Democrats (63%). The Wait and Learn group, compared to the Intenders, were less likely to report being diagnosed with a high risk condition for COVID-19, receiving an influenza vaccine in the past 12 months, discussing COVID-19 vaccine with their healthcare provider, perceiving COVID-19 as severe, considering a COVID-19 vaccine important to stop the spread of infection, and wering a mask usually or almost always. Conclusion: Only half of US adults intend to accept COVID-19 vaccines; most others (40%) are uncertain. Levels of immunity associated with community protection will not be achieved without reaching those who are currently uncertain. Characterizing COVID-19 vaccine attitudes and intentions and ascertaining values and trust in local, state, and federal public health authorities that impact vaccine decision-making are essential.